Opinion on monoaminergic contributions to traits and temperament - Robbins, T. W. (Philos Trans R Soc Lond B Biol Sci, 2018)
This article critically reviews evidence relating temperamental traits and personality factors to the monoamine neurotransmitters, especially dopamine and serotonin. The genetic evidence is not yet considered to be conclusive and it is argued that basic neuroscience research on the neural basis of behaviour in experimental animals should be taken more into account. While questionnaire and lexical methodology including the ‘Five Factor’ theory has been informative (mostly for the traits relevant to social functioning, i.e. personality), biologically oriented approaches should be employed with more objective, theoretically grounded measures of cognition and behaviour, combined with neuroimaging and psychopharmacology, where appropriate. This strategy will enable specific functions of monoamines and other neuromodulators such as acetylcholine and neuropeptides (such as orexin) to be defined with respect to their roles in modulating activity in specific neural networks—leading to a more realistic definition of their interactive roles in complex, biologically based traits (i.e. temperament). This article is part of the theme issue ‘Diverse perspectives on diversity: multi-disciplinary approaches to taxonomies of individual differences’.